2012
DOI: 10.1007/s00348-011-1259-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatial filter velocimetry based on time-series particle images

Abstract: High accuracy and high spatial resolution are required in measurements of fluid velocity for detailed flow diagnostics. In this study, we proposed spatial filter velocimetry (SFV) based on a frequency analysis of timeseries spatially filtered particle images. Since this method can measure velocity from one particle in a measurement region, it enables us to measure the velocity with high accuracy and high spatial resolution. We developed a SFV system and applied it to laminar and turbulent flows in a duct to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…In this study, we use a cosine function for F SF , and a wavelet analysis is adopted to evaluate the frequency of I SF . Details of SFV can be found in Hosokawa and Tomiyama (2012).…”
Section: Principle Of Spatiotemporal Filter Velocimetrymentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we use a cosine function for F SF , and a wavelet analysis is adopted to evaluate the frequency of I SF . Details of SFV can be found in Hosokawa and Tomiyama (2012).…”
Section: Principle Of Spatiotemporal Filter Velocimetrymentioning
confidence: 99%
“…Hence, an accurate measurement of interfacial shear stresses in both phases would enable us to evaluate the Marangoni stress. Imaging velocimetry such as PIV and spatiotemporal filter velocimetry (SFV; Hosokawa and Tomiyama 2012;Hosokawa et al, 2013) may provide velocity distributions in the vicinity of an interface. However, the presence of an interface in a measurement region decreases the measurement accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, high-speed video cameras can be used to image the gas-liquid flow field. Hosokawa et al (2012a) used spatial filter velocimetry (SFV) based on spatial filtering of timeseries particle images proposed by Hosokawa and Tomiyama (2012b) to examine multiscale bubble velocity measurement. The edge detection process is added in the SFV processing to reduce the size of the image pattern and to obtain accurate velocity data; it demonstrated that SFV is able to measure bubble velocity in various spatial scales with higher accuracy than PIV and was successfully comparable to optical probe measurements.…”
Section: Introductionmentioning
confidence: 99%
“…SFV has been applied, for example in detecting surface velocities (Schaeper and Damaschke 2011), length (Bergmann 2010), fluid flow (Hosokawa and Tomiyama 2011), or the microcirculation of blood cells in the capillaries of human fingernail folds (Menn 2011). In the latter application, the shape of the spatial filter had to be adapted to the structure of the capillaries in the proximal nail folds of the fingers.…”
Section: Introductionmentioning
confidence: 99%